JNK Signalling: A Possible Target to Prevent Neurodegeneration - Tiziana Borsello; Gianluigi Forloni (Current Pharmaceutical Design, 2007)
The c-Jun N-terminal kinases (JNK) belong to the subfamily of mitogen-activated protein kinase (MAPK). JNK is an important transducing enzyme that is involved in many facets of cellular regulation including gene expression, cell proliferation and programmed cell death. The activation of JNK pathways is critical for naturally occurring cell death during development as well as for pathological death associated with neurodegenerative diseases. Initial research concentrated on defining the components and organization of JNK signalling cascades, but more recent studies see JNK as a target to prevent cell death. Several in vitro and in vivo studies have reported alterations of JNK pathways potentially associated with neuronal death in Parkinson's and Alzheimer's disease. So efforts are now aimed at developing chemical inhibitors of this pathway. These have proved effective in vivo, reducing brain damage and some of the symptoms of arthritis in animal models. An alternative cell penetrating peptide approach is now available, with the identification of the JNK permeable peptide inhibitor, which modifies JNK action rather than activation, preventing neuronal death with unprecedented specificity and efficacy in several experimental conditions, including two animal models of ischemia. In this review we examine in detail the role of JNK in neurodegeneration, particularly in Alzheimer's and Parkinson's disease. The possibility of intervention on the JNK pathway as a therapeutic approach is also illustrated.
Keywords: c-Jun N-terminal kinase